2018
DOI: 10.5658/wood.2018.46.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Method of DNA Extraction from Pinus rigida Wood Pretreated with Sandpaper

Abstract: Species identification of wood provides important information for archaeology, restoration of cultural assets, preventing illegal logging, and more. Wood species are usually identified based on their anatomical features with the use of a microscope. However, this method may not be able to distinguish between anatomically similar species or subspecies. To overcome this problem, wood species need to be identified at the molecular level using DNA sequencing. However, unlike living plant cells, wood is difficult t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, matK, rbcL, rpoB, and ycf1 were suggested as genes for DNA barcoding [31][32][33]. matK and rbcL were suggested as DNA barcodes for land plants by the Consortium for the Barcode of Life-Plant Working Group [34]. rpoB was suggested to be more efficient in family level identification than genus level identification [35].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, matK, rbcL, rpoB, and ycf1 were suggested as genes for DNA barcoding [31][32][33]. matK and rbcL were suggested as DNA barcodes for land plants by the Consortium for the Barcode of Life-Plant Working Group [34]. rpoB was suggested to be more efficient in family level identification than genus level identification [35].…”
Section: Introductionmentioning
confidence: 99%